A FLAP MODALITY FOR RESURFACING FOLLOWING EXTERNAL GENITALIA TUMOR ABLATION: A CONSECUTIVE CASE SERIES - Muzakkie, Mufida; Amatullah Sakinah, Annisaa Nabila (Jurnal Plastik Rekonstruksi, 2023)
Introduction : External genitalia defect may result from various cases such as vulvar cancer, cervical cancer, tumor metastases, etc. Female genitalia is challenging for reconstruction due to many complex anatomical structure like urethra, vagina, anus, and its a highly mobile region. It is need to reconstruct with high successful rate and low morbidity procedure. The aim of this paper is to report various flaps for resurfacing following external genitalia defect. Method : From September 2017 - April 2022, 7 patients referred by Obstetric Gynecology Department to Plastic Surgery Division at Muhammad Hoesin Central General Hospital. The data was reviewed retrospectively to evaluate demographic, diagnosis, choice of flap reconstruction, functional and anatomical long term evaluation. Result : The ages of the patients ranged from 29 - 67 year-old, diagnosed with cervical cancer with tumor metastases to vulva in 16% (n=1) and vulvar carcinoma 84% (n=5). Flaps performed: Antero-lateral Thigh (ALT) flap in 14,5% (n=1), gracilis flap in 28,5% (n= 2), rotation flap in 28,5% (n= 2), keystone flap in 28,5% (n=1). A major dehiscence and need required reoperation for abscess in 16% (n=1). Flap selection based on size, region, and anatomical structure defect. ALT was chosen for wide and bilateral vulvar and perineal defect, gracilis for unilateral vulvar and perineal defect, Keystone flap for half of vulvar and perineal defect, rotation flap for defect on mons region. Conclusion: Flap selection in genitalia external reconstruction must be consider on the anatomical loss structure and defect size to achive durable tissue for acceptable functional and mobilisation. The algorithm may help to choose for flap based on loss area.